Hubungan antara produksi Udang Vaname dengan pengeluaran konsumsi pangan, pendidikan dan kesehatan di Kabupaten Kolaka - Maun, Raus Hidayat; Budiyanto; Riani, Irdam; Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2023)
The purpose of this study was to determine the relationship between vannamei shrimp production and expenditure on food consumption, education and health in Kolaka Regency. The experiment was conducted from March to April 2021. The population of shrimp farmer in this study was 32 shrimp farmer and technical for samples collection used a saturated sampling technique. Data collection was obtained through observation, interviews and documentation. Data were analyzed using the correlation formula. The results showed that there was a moderate relationship between production and food and health consumption expenditures. While the relationship between production and education spending has less significant relationship criteria